2003
DOI: 10.1303/aez.2003.571
|View full text |Cite
|
Sign up to set email alerts
|

Flower visitors of lettuce under field and enclosure conditions

Abstract: Insects visiting lettuce flowers were investigated under field and enclosure conditions. In a 4-year field survey, visitors of 11 species belonging to 3 orders were observed. Most species visiting the flowers were sweat bees (Hymenoptera; Halictidae). The frequency (total days of visitation to lettuce flower/total days of flight by the insect) of visitations by the sweat bee Lasioglossum villosulum trichopse was obviously higher at 65.5% than those of other insects. Honeybees were not observed on the lettuce f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 26 publications
(27 reference statements)
0
13
0
1
Order By: Relevance
“…The importance of pollinators for the effective pollination of Lactuca flowers has already been demonstrated (Goubara et al, 2003;. Jones (1927), showed that bagged flowers of L. sativa had significantly less or no pollen grains on their inner stigmatic surfaces, compared to open-pollinated flowers.…”
Section: Importance Of Pollinators For Gene Flow In Lettucementioning
confidence: 96%
See 1 more Smart Citation
“…The importance of pollinators for the effective pollination of Lactuca flowers has already been demonstrated (Goubara et al, 2003;. Jones (1927), showed that bagged flowers of L. sativa had significantly less or no pollen grains on their inner stigmatic surfaces, compared to open-pollinated flowers.…”
Section: Importance Of Pollinators For Gene Flow In Lettucementioning
confidence: 96%
“…Moreover, they have an influence on seed set (Mejias, 1994). Not surprisingly, distance and pollinator availability have been found to be the most relevant factors for pollen migration between different L. sativa varieties (Goubara and Takasaki, 2003;Thompson et al, 1958). While wild × crop hybridization cannot be inferred directly from the results presented above, we can assume that the main factors influencing the pollination of prickly lettuce by the crop are the same, since the species are very closely related.…”
Section: D'andrea Et Almentioning
confidence: 99%
“…This ground-nesting bee is a species native to our field where various kinds of flowering plants (lettuce cultivars and their allied species belonging to the tribe Lactuceae) are cultivated in 24.0 or 24.5 cm plastic pots as foraging resources for the insects (Goubara and Takasaki, 2003). Setting 'bee-beds', wooden boxes filled with clay soil and sand, on the ground for the nesting substrate, we commenced the rearing of sweat bees in 1995 in an arched, vinyl-roofed cage (7.0ϫ7.0ϫ3.5 m in height of top) and continued in 1998 in the field.…”
Section: Insects and Plantsmentioning
confidence: 99%
“…'V', 'Summer Red' and 'Tima Santyu' were contained in 16, 11 and 19 pots, respectively, in the field, and 10 pots of each were set in the cage. Eight species of bees, including L. villosulum trichopse, in about 270 nests were reared in the cage (Goubara and Takasaki, 2003). On the other hand, seven species of bees, not including L. villosulum trichopse, were reared in the field.…”
Section: Insects and Plantsmentioning
confidence: 99%
See 1 more Smart Citation